Ensino de conceitos a uma criança com deficiência visual por meio de brincadeira - Ferroni, Giovana Mendes (2012)
The development of teaching strategies and learning concepts for visual impaired children has been a challenge in researches and educational purposes. The objective of this study was to investigate the handling of toys for a child with multiple disabilities (visual impairment and associated disability) could occur in a teaching strategy that would be beneficial to the learning concepts. Therefore it was made a teaching environment with educational toys and games that were used to provide enjoyable and meaningful opportunities for the child, thus benefiting the conditions for the learning concepts. It has participated on this study a five year old girl in the beginning of the research , with multiple disabilities (visual impairment and associated disability), with unconfirmed diagnosis of toxoplasmosis after-effects and cytomegalovirus, who attended an institution of a medium-sized city of the State of Sao Paulo. Interviews were conducted with the mother of the participant and recorded in audio, familiarization sessions and teaching conditions were recorded in video as well. Four of the intervention sessions were examined in order to identify the parameters of analysis and define the episodes in which the context indicated the child's participation in the game with the experimenter and the her interaction with the toy. It was created categories of analysis considering the learning concepts, the actions of the adult and the child's actions in the games planned. Data analysis indicated that the participant played actively and showed satisfaction in activities of non-voice signals, such as shaking the body, beating the hands on the sides of her legs, shaking the head and clapping. Moreover, the adult's action, to contextualize the gestures and body movements from the participant, and the usage, for example, of the anticipation of what would happen in the environment, allowed the child to participate and remain in the game. In the situations in which the child didn't want to play, she turned her head to the opposite side of the experimenter or of the object that had been offered, or they sometimes said "not", or even shook the body from one side to the other, that could be interpreted as impatience, and muttered "Ãaaaaah" or "Iiihhhhh" or "Aaooo" or "Uuuu". The data indicated the importance of an adult mediation during the activities, so he could highlight and orientate the child's attention to: the objects that were at her disposal, the changes she could cause in the toys / objects during handling; the modifications that the objects produced in the environment, and the possibility of repeating the changes produced in the object and the environment. Furthermore, it was considered important that the adult was aware of the context of the game and the usage of the toys in a context. From the data obtained it was allowed to consider the context of games beneficial to the conditions of learning concepts by children with visual impairment and it also reaffirmed the importance of an adult sensitive to the clues offered by the child to create and develop appropriate conditions that promote learning.